PENGARUH KECERDASAN INTELEKTUAL, KECERDASAN EMOSIONAL DAN KOMUNIKASI INTERPERSONAL TERHADAP LOYALITAS KERJA GURU PADA SMA NEGERI 7 OKU DI KECAMATAN PENINJAUAN KABUPATEN OGAN KOMERING ULU - Malini, Hema; Yunsepa, Yopi; Nurlaila, Nurlaila (KOLEGIAL, 2023)
This study aims to determine the influence of intellectual intelligence, emotional intelligence and interpersonal communication at SMA Negeri 7 OKU in Peninjauan District, Ogan Komering Ulu Regency. In this study the method used is descriptive method and accidental sampling with a total sample of 49 respondents. By using multiple linear regression analysis, correlation coefficient analysis, the coefficient of determination hypothesis testing (t test and F test) and to test the research hypothesis used f test and t test. The results of the Determination Test obtained the contribution of the variables of intellectual intelligence (X1), emotional intelligence (X2) and interpersonal communication (X3) to teacher loyalty (Y), it was stated that the relationship was very strong, while the value of the coefficient of determination (R Square) was 0.857 or 85.7% . This value indicates that the contribution of the independent variables Intellectual Intelligence, Emotional Intelligence and Interpersonal Communication is 85.7% of the dependent variable Teacher Work Loyalty. Meanwhile, the remaining 14.3% is contributed by other factors not examined.